Intermediate fragmentation surrounding vineyards favours the Coleoptera community within the crop. (1st July 2022) - Taranto, Luisa; Rodrigues, Isabel; Santos, Sónia; Villa, María; Pereira, José Alberto
Abstract: Insects of the order Coleoptera play an essential role in agricultural sustainability by supporting many ecosystem services (such as biological control, nutrient cycling or pollination). In agroecosystems, the Coleoptera community may be influenced by the surrounding landscape, which can provide living resources, like food or shelter, during different seasons, originating spillover movements between different environments. The present study aimed to evaluate the response of the Coleoptera community to the landscape surrounding vineyards at different buffers. For that, Coleoptera were sampled in six wine protected designation of origin (PDO) regions of Portugal (35 vineyards), and landscape configuration and composition metrics were calculated at buffers of 500, 750, 1000, 1500 and 2000 m radii around the vineyards. In total, 2954 Coleoptera individuals belonging to 36 families were collected. The most abundant families were Chrysomelidae, Coccinellidae and Latridiidae. Results indicated that intermediate habitat fragmentation levels, particularly in semi‐natural areas and vineyards, favoured Coleoptera biodiversity in vine‐producing regions. Moreover, the range of activity of Coleoptera seems to be larger than 1000 m. This work constitutes an important contribution to understanding the response of the Coleoptera community to the landscape context in vineyards in Portugal and contributes to the theoretical framework about the influence of habitat fragmentation on biodiversity.